Identification, Pathogenicity, and Fungicide Sensitivity of Colletotrichum Species Associated with Anthracnose on Italian Ryegrass in Southwestern China - Xu, Lingling (Plant disease, 2024)
Italian ryegrass (Lolium multiflorum L.) is widely cultivated as an important forage grass worldwide because of its high nutritional value and good palatability. Anthracnose caused by Colletotrichum species was a common and new emerging disease of Italian ryegrass. In this study, 88 Colletotrichum isolates were collected from diseased leaves of Italian ryegrass planting regions in Sichuan, Chongqing, and Guizhou provinces of southwestern China between 2019 and 2022. By the pure culture technique, 15 representative single-spore isolates were obtained for further study. Multilocus phylogenetic analysis coupled with morphological features showed that these isolates were finally identified as six new record species: C. cereale of the C. graminicola species complex, C. fioriniae and C. nymphaeae of the C. acutatum species complex, C. boninense and C. citricola of the C. boninense species complex, and C. nageiae. Pathogenicity tests indicated that all species could induce anthracnose symptoms; of these, C. cereale was more invasive than other species, followed by C. fioriniae, C. nageiae, C. citricola, and C. boninense; C. nymphaeae was the weakest pathogenic species to Italian ryegrass plants (P ≤ 0.05). Fungicide sensitivity assays showed that iprodione, propineb, and oxime·tebuconazole had strong inhibitory effects on the mycelial growth of six Colletotrichum species; in addition, azoxystrobin and fludioxonil also significantly inhibited the mycelial growth of C. nymphaeae and C. fioriniae, respectively. These results provide the basis for the diagnosis and detection in the field, pathogen identification, and management of anthracnose on Italian ryegrass